Assessment of Empowerment of Women Farmers in Decision Making in Agriculture and Livestock Activities - Parvez Hussain Sahito; Ameer Ali Abro; Mukesh Kumar Khatwani (Journal of Management Practices, Humanities and Social Sciences, 2021)
In Pakistan, women constitute about 67% of the agricultural labor force, engaged in agriculture and its sub-sectors to support their families. Because of the patriarchal society, women have been discriminated against in acquiring fundamental rights and decision-making in numerous aspects of life, including various farm and livestock-related activities. No or very limited studies have been conducted regarding women farmers' empowerment, especially in the Ghotki, Naushahro Feroz, and Badin districts of Sindh. Hence, this qualitative study was carried out in districts Ghotki, Naushahro Feroz, and Badin, Sindh to determine women farmers' perceptions about their empowerment regarding decision-making in agriculture activities. Thirty IDIs and nine FGDs were conducted through purposive sampling, and the collected data were analyzed through thematic analyses. This study reveals that women farmers perform various agricultural and livestock tasks for about 6 to 8 hours a day with their man folks. Illiteracy and poverty were the main reasons behind their engagement in the sector, and they worked as unpaid labour with their men. Women farmers have limited decision-making authority in various crop activities, the sale and purchase of agricultural goods, livestock, and its by-products, due to cultural constraints, they have no access to the agricultural market. This study suggests that education, professional training, and property ownership rights may be provided to women farmers to grow economically and be productive for future generations, society, and the country.